Stress in the nursing academic life. (Un) awareness and prevention - da Silva Philbert, Larissa Angélica; Corral-Mulato, Sabrina; Antoniassi Baldissera, Vanessa Denardi; Luiza dos Santos, Janaina; Villela Bueno, Sonia Maria (Investigación y Educación en Enfermería, 2011)
Objective. To describe the personal and professional perceptions of stress, prevention and issue approach in training Brazilian nursing students. Methodology. A qualitative, descriptive-exploratory study was developed in the year of 2009, through an open survey application. Answers were analyzed through thematic analysis categorizing identified qualitative variables. Results. Eight female students in their last year of nursing school with ages between 21 and 27 years old participated. Personal stress is related to unbalanced situations and difficulties in their professional life, work overload, and lack of vocation, they all have physical and mental manifestations. Conclusion. Participants related personal stress with unbalanced situations and difficulties in the professional life, work overload and lack of vocation.